PENGARUH PENGETAHUAN PERPAJAKAN DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM SESUAI PP 23/2018 DI KPP PRATAMA MALANG SELATAN - Ria Novitasari; Noor Shodiq Askandar; Abdul Wahid Mahsuni (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The purpose of this study was to determine the effect of tax knowledge and socialization on taxpayer compliance on KPP Pratama Malang Selatan. The population of this study is taxpayer KPP Pratama Malang Selatan. The sample used is 95 samples that meet the criteria in the research subject yaer 2021. The analysis method used is multiple regression equation, normality test, classical assumption test., descriptive statistical analysis and hypothesis testing. The results show that tax knowledge and tax socialization affect taxpaer knowledge in KPP Pratama Malang Selatan.Keywords : Tax Knowledge, Tax Socialization, and Taxpayer Compliance.